Using names as a measure of cultural diversity among radiology residents in the United States - Ali Rastegarpour; Hai Hoang; Hakob Kocharyan (Shahid Beheshti University of Medical Sciences, 2024)
Background: Names can potentially carry pertinent information regarding cultural background and familial socioeconomic and educational status. This study was performed to utilize first names as a measure of cultural diversity, and in addition, describe the frequency and distribution of women and international medical graduates in radiology residency in the United States. Methods: The websites of all 181 ACGME accredited diagnostic radiology residency programs were evaluated to extract the first name, gender, and medical school (US medical graduate or international medical graduate) of residents. These names were compared with the 100 most common names for girls and boys from each decade from 1940 through 2000 from the Social Security website. Results: The websites from 151 programs included information for a total of 4083 residents. Female residents constituted 25.0% of all radiology residents. International medical graduates constituted 11.7%. Overall 37.5% of the residents had uncommon names, including 32.0% of US medical graduates. There was no significant association between having a female program director with a higher number of female residents (p=0.153). In addition, there was no significant correlation between program directors with uncommon names and residents with uncommon names (p=0.691). International medical graduates were more prevalent in the Northeast and Midwest, corresponding to the higher overall percentage of non-common names. However, uncommon names were also higher in the same regions after excluding international medical graduates. Female radiology residents demonstrated higher percentages in the West, Southwest, and East. Conclusion: Names may represent an index of cultural diversity. Further investigation may prove useful.